Mudharabah sebagai Alternatif Pembiayaan yang Potensial untuk Peningkatan Pengembangan pada UMKM - Marianingsih, Ita; Rosiki, Hoirur (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Mudharabah is a form of contract or agreement between two parties, namely investors (owners of capital) and entrepreneurs (managers of capital). In this contract, investors will provide capital and entrepreneurs known as business managers will use this capital to develop their businesses. The profit generated will be shared according to the agreement between the two parties, while the loss will be borne by the owner of capital (investor) but if negligence is caused by the manager of capital (entrepreneur), the loss will be borne by the manager of capital. Through mudharabah, MSMEs can get access to greater capital to develop their business. Even though there are risks for investors, on the other hand, business managers can execute their vision and develop their business with lower risk. This study uses descriptive qualitative, namely using literature studies cited from relevant books and websites. The purpose of this study is to encourage MSME actors to continue to improve the quality of their work so that they can become a forum for reducing unemployment in Indonesia and so they can compete in the global market. Lack of funds for MSMEs has become commonplace, but mudharabah is here as an alternative financing for development of MSMEs, so it is hoped that MSME actors will be smart in managing existing capital with this mudharabah financing. Keywords: Mudharabah, MSME